Design and simulation of impluse voltage generator - M., Jayaraju; Mohd Rafi, Adzman; Noor Hasnizam, Hanafi; Mohammad Faridun Naim, Tajuddin; Siti Rafidah, Abdul Rahim; Syahrul Ashikin, Azmi (Malaysian Technical Universities Network (MTUN), 2011)
3rd Malaysian Technical Universities Conference and Exhibition on Engineering and Technology (MUCEET 2009) organized by Malaysian Technical Universities Network (MTUN) comprising of Universiti Malaysia Perlis (UniMAP), Universiti Tun Hussain Onn Malaysia (UTHM), Universiti Teknikal Malaysia Melaka (UTeM) and Universiti Malaysia Pahang (UMP), 20th - 22nd June 2009 at Kuantan, Pahang, Malaysia.